The Effect of Working Capital Turnover, Debt to Asset Ratio and Times Interest Earned on Profitability - Siti Kustinah; Rifa andinie (Profesional Muda Cendekia Publishing, 2023)
The purpose of this research is to identify and analyze the influence of variables on each property and real estate company listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The indicators used in this study are Working Capital Turnover (WCTO), Debt to Asset Ratio (DAR), Times Interest Earned (TIE) and Profitability (ROA). The population in this study were 80 companies and 44 companies as a sample with a total of 220 observations. This research uses purposive sampling method with five observation periods. This research uses descriptive quantitative method and associative method then multiple linear data analysis using SPSS 25 application assistance, this research uses independent variables, namely working capital turnover (WCTO), debt to assets ratio (DAR) and times interest earned (TIE) and the dependent variable is profitability (ROA). Based on data processing the results of this study show that partially working capital turnover (WCTO) has no significant effect on profitability, Debt to Asset Ratio (DAR) has no significant effect on profitability, times interest earned (TIE) has a positive and significant effect on profitability, Overall Simultaneous variables Working Capital Turnover (WCTO), Debt to Asset Ratio (DAR) and Times Interest Earned (TIE) have a significant effect on profitability (ROA).